There ís water A traveller's view of the Xhariepean community in transition - Teck, Lut (UJ Press, 2014)
This unique trilingual publication offers a traveller's view of the people of the Xhariep and their daily lives. The book results from a research project in the southern Free State, 'Multilingualism for Empowerment', that was undertaken with the financial assistance of the Province of Antwerp in Flanders, Belgium, and in collaboration with the University of Antwerp. The book entails a collection of journal entries, photographs, interview material and background information recorded by Lut Teck, a Flemish member of the research team, during her field work in the area.